Organizational behavior and the inclusion of people with disabilities (PWD): ¿a possible relationship? (AACINI - International Journal of Industrial Engineering, 2024)
The labor inclusion of People with Disabilities (PWD) is imposed as a topic to be studied given that the social group is changing its behavior in several aspects in relation to minorities. Which imposes an intervention from field research immediately. This article aims to share with the scientific community advances resulting from exploratory actions carried out from 2021 to date. For this survey, the state of the art of the problem is presented in light of the research questions that guide it. The main objective of the work is to investigate in specialized bibliographic sources which are the models of Organizational Behavior that allow the topic to be addressed. Data processing is carried out through a two-way analysis of sources, using primary and secondary sources to meet the stated objective. It is expected with such a contribution to provide data that accounts for the labor inclusion of PWD that ensures being able to contribute to the knowledge of behavior in the context of organizations and their perspective of evolution.
Keywords: organizational behavior; people with disabilities; labor inclusion